Commonwealth Edison : the use of social media in disaster response - Diermeier, Daniel; Petrella, Daniel ([London] : SAGE, 2016)
After a massive storm hit the northern Illinois service area of electric utility Commonwealth Edison on July 11, 2011, more than 900,000 customers were left without power during a hot, humid summer. ComEd crews and reinforcements from more than a dozen other states worked for days afterward to restore service. Meanwhile, the company's months-old social media strategy faced its first major test. This case examines the company's efforts to engage with their customers through social media.
Originally Published in: Diermeier, D., & Petrella, D. (2013). Commonwealth Edison: The Use of Social Media in Disaster Response. 5-212-251. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Commonwealth Edison Company; Customer relations -- Case studies; Social media -- Case studies; Crisis management -- Case studies